2014
DOI: 10.4081/ejh.2014.2263
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of VEGFR2 inhibits proliferation and induces apoptosis in hemangioma-derived endothelial cells

Abstract: Angiogenesis is a process of development and growth of new capillary blood vessels from pre-existing vessels. Angiogenic growth factors play important roles in the development and maintenance of some malignancies, of which vascular endothelial growth factor (VEGF)/VEGFR2 interactions are involved in proliferation, migration, and survival of many cancer cells. The aim of this study was to investigate the function of VEGFR2 in human hemangiomas (HAs). Using immunohistochemistry assay, we examined the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
4
28
0
1
Order By: Relevance
“…The characteristics of HDEC were listed as follows: the nucleus of HDEC was very clear, the cells showed long spindle and polygonal, and the "vessel cavity" structure could be formed. The positive expression of PCNA and VEGF was confirmed to be increased in proliferating phase HAs but decreased in involuting phase HAs as previously reported [5,6,23]. HDEC and CRL-2586 EOMA cell lines were cultured in Dulbecco's Modified Eagle's medium (DMEM, Sigma, Aldrich, USA) supplemented with 10% heat-inactivated Fetal Bovine Serum (FBS, Sigma, Aldrich, USA), 100U/ml of penicillin and 100μg/ml of streptomycin (Invitrogen, Carlsbad, CA, USA), and were placed in a humidified atmosphere containing 5% CO2 at 37°C.…”
Section: Cell Isolation Culture and Transfectionsupporting
confidence: 87%
See 4 more Smart Citations
“…The characteristics of HDEC were listed as follows: the nucleus of HDEC was very clear, the cells showed long spindle and polygonal, and the "vessel cavity" structure could be formed. The positive expression of PCNA and VEGF was confirmed to be increased in proliferating phase HAs but decreased in involuting phase HAs as previously reported [5,6,23]. HDEC and CRL-2586 EOMA cell lines were cultured in Dulbecco's Modified Eagle's medium (DMEM, Sigma, Aldrich, USA) supplemented with 10% heat-inactivated Fetal Bovine Serum (FBS, Sigma, Aldrich, USA), 100U/ml of penicillin and 100μg/ml of streptomycin (Invitrogen, Carlsbad, CA, USA), and were placed in a humidified atmosphere containing 5% CO2 at 37°C.…”
Section: Cell Isolation Culture and Transfectionsupporting
confidence: 87%
“…Low expression of MEG3 acts as an independent factor for predicting poor prognosis in cancer patients [12,15,25,26], and the downregulation of MEG3 is attributed to its promoter hypermethylation in cancer [27][28][29], and the negative modulation by DNMT1 in glioma [30]. MEG3 and VEGF have the differential expression levels in HAs [5,18]. In the present study, we found that, MEG3 expression was decreased and harbored the negative association with VEGF expression in proliferating phase HAs rather than in the involuting phase HAs, suggesting that MEG3 might be a negative regulator of HAs proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations